2019
DOI: 10.1080/14786419.2019.1679139
|View full text |Cite
|
Sign up to set email alerts
|

(R)-3-(8'-Hydroxyfarnesyl)-indole and other chemical constituents from the flowers of Anomianthus dulcis and their antimalarial and cytotoxic activities

Abstract: 3-(8'-Hydroxyfarnesyl)-indole and other chemical constituents from the (R)-3-(8'-Hydroxyfarnesyl)-indole and other chemical constituents from the flowers of Anomianthus dulcis and their antimalarial and cytotoxic activities flowers of Anomianthus dulcis and their antimalarial and cytotoxic activities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Pinocembrin is a flavonoid that can be isolated from propolis (bee glue) and plants in several families, for example, Piperaceae, Lauraceae, and Asteraceae. 5 It can also be biosynthesized using microorganisms and chemical reactions. 17 - 19 Our previous study reported a successful isolation of several flavonoids, including pinocembrin, from A. dulcis , a species belonging to the Annonaceae family.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pinocembrin is a flavonoid that can be isolated from propolis (bee glue) and plants in several families, for example, Piperaceae, Lauraceae, and Asteraceae. 5 It can also be biosynthesized using microorganisms and chemical reactions. 17 - 19 Our previous study reported a successful isolation of several flavonoids, including pinocembrin, from A. dulcis , a species belonging to the Annonaceae family.…”
Section: Discussionmentioning
confidence: 99%
“…It is indigenous to Southeast Asia and can be found in woods or grasslands of the Northeast of Thailand. 4 , 5 The flowers are salmon-pink, with a strongly sweet smell, and the fruit is edible ( Figure 1A ). The decoction of its stems and roots is used as an antipyretic and galactagogues in traditional Thai medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new farnesylindole alkaloid was obtained from the flowers of Anomianthus dulcis (Dunal) J. Sinclair (Annonaceae) and was named (R)-3-(8'-hydroxyfarnesyl)-indole (63) [109]. The structure of the new compound is very similar to a known compound 3-(R)-3-(8'-hydroxyfarnesyl)-indole, differing by the presence of a hydroxyl in the new compound.…”
Section: Alkaloidsmentioning
confidence: 97%
“…Thus, 3-farnesylindole ( 90 , Fig. 17) was isolated from Anomianthus dulcis in 33% ee in favour of the R -enantiomer, 124 and the marine furanoditerpene 12-hydroxyambliofuran ( 91a ) and its acetate ( 91b ) were obtained from a Spongia species as a ca. 3 : 1 mixture of enantiomers.…”
Section: The Origin Of Scalemic Natural Productsmentioning
confidence: 99%